REST vs. SOAP : the battle of the web service titans picking a winning web service approach. - Hinchcliffe, Dion
At their most basic level, Web services work well and solve important problems because they are based on standards. However choosing among the available Web service approaches can still be surprising difficult. Whether it is correct or incorrect, the choice will have far reaching consequences for any project. A foray in the wrong direction often means having to abandon the initial investment, in terms of development, training and infrastructure, to retool everything to go another way. Make a good decision through and Web services become an enabling springboard to enterprise integration, information self-service and all the attendant benefits of service oriented architecture. In a highly competitive business environment, the risk of lost time and investment means that making the best decision up front is vital to success.